“Integrating Digital Portfolios to Enhance Artistic Competencies in Grades 5–7 Visual Arts Lessons” - Axmedov Dilmurod Xolmamatovich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article examines the use of digital portfolios in grades 5–7 visual arts lessons to enhance students’ artistic competencies, creativity, and reflective skills. The study shows that maintaining digital portfolios encourages students to document their progress, reflect on their learning process, and experiment with various artistic techniques. The integration of digital portfolios promotes self-assessment, collaborative feedback, and active engagement, providing an innovative approach to visual arts education.